Resistant Starch : Pembentukan, Metabolisme, dan Aspek Gizi-nya - Y. Marsono (agriTECH, 1998)
"Resistant starch (=RS)" is defined as the sum of starch and products of starch degradation not absorbed in the small intestine of healthy individuals. The presence of RS can be influenced by some factors including processing, the type of starch (amylase or amylopectin), the physical state of the starch (degree of hydration, particle size) and the presence of other components (i.e. lipids and fiber). in the large intestine, RS is fermented (as dietary fiber) by anaerobic bacteria. The major end product of fermentation are Short Chain Fatty Acids (SCFAs: acetate, propionate and butyrate) and gases (CH4, CO2 and H2.). The important physiological effects of RS are due not to the RS itself but also the SCFAs. Among the physical properties of RS are increase the viscosity of the intestinal content, reduce the rate of small intestinal absorption and increase stool bulk and fecal weight. Butyrate which is one of the main end products of fermentation is believed to protect against colorectal cancer while propionate has been suggested to play a certain role in the lipid metabolism. SCFA is also known to decrease pH of the intestinal content which make the large intestine healthier.